2017
DOI: 10.1016/j.celrep.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of NOD2 Receptor Converts Inflammatory Ly6C high into Ly6C low Monocytes with Patrolling Properties

Abstract: The signals that regulate the fate of circulating monocytes remain unknown. In the present study, we demonstrate that triggering of the NOD2 receptor by muramyl dipeptide (MDP) converts inflammatory Ly6C monocytes into patrolling Ly6C monocytes. Administration of MDP to Nr4a1 mice, which lack Ly6C monocytes, or to Ly6C-depleted mice led to the emergence of blood-patrolling monocytes with a profile similar to that of Ly6C monocytes, including high expression of CX3CR1 and LFA1. Using intravital microscopy in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 50 publications
4
71
0
1
Order By: Relevance
“…We also confirmed that treatment of infected mice with MDP markedly increases the presence of Tregs to the lungs of mice (Figures 6 B,C). This is consistent with our previous report showing that MDP treatment induces the conversion of blood Ly6C high monocytes into Ly6C low monocytes and consequently their number in the circulation ( 52 ). Presence of Tregs in lungs of mice also coincides with the optimal production of CXCL12, CCL5 and TGF-β in lungs of IAV-infected mice treated with MDP compared to mice treated with a placebo (Figures 6 D–F).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…We also confirmed that treatment of infected mice with MDP markedly increases the presence of Tregs to the lungs of mice (Figures 6 B,C). This is consistent with our previous report showing that MDP treatment induces the conversion of blood Ly6C high monocytes into Ly6C low monocytes and consequently their number in the circulation ( 52 ). Presence of Tregs in lungs of mice also coincides with the optimal production of CXCL12, CCL5 and TGF-β in lungs of IAV-infected mice treated with MDP compared to mice treated with a placebo (Figures 6 D–F).…”
Section: Resultssupporting
confidence: 94%
“…We have previously reported that Ly6C low patrolling monocytes are important for trafficking of Treg cells in a mouse model of arthritis and that in vivo administration of MDP increases levels of Ly6C low monocytes in the blood of mice ( 51 , 52 ). We wanted to determine whether Ly6C low monocytes are essential to Treg recruitment in lung of mice during IAV infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our data suggest a redundancy between Ly6C low and Ly6C high monocytes for the endothelial repair process. Recently, it was shown that Ly6C high monocytes can be converted into Ly6C low monocytes with endothelial patrolling properties . Such a conversion may explain why neither monocyte subtype (Ly6C high or Ly6C low ) is solely required for the endothelial repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Similar activation results upon MDP treatment were also observed in human DCs differentiated in vitro using mononuclear bone marrow cells purified from acute leukaemia patients. 140 More broadly, MDP was shown to elicit the migration of Ly6C high monocytes from the bone marrow to the lungs 141 and to convert inflammatory, Ly6C high monocytes into Ly6C low monocytes that exhibit patrolling properties, 142 highlighting the complex and likely simultaneous activities of MDP in systemic circulation on myeloid cell populations.…”
Section: Peptidoglycan Metabolites and Cancer Treatmentmentioning
confidence: 99%